13.1 Orthography and Orthoepy - Gonçalves, Maria Filomena (2020)
In 1990, Portugal, Brazil, and the then-five (now six) African countries whose official language is Portuguese (Cape Verde, Guinea-Bissau, São Tomé and Príncipe, Angola, and Mozambique) signed the Acordo Ortográfico de 1990 (AO90), an international agreement whose objective it is to give Portuguese – a pluricentric language – a common orthography. The AO90 has gone through some difficulties and is now official only in four Lusophone countries (Portugal, Brazil, Cape Verde, and São Tomé and Príncipe). However, after centuries without an official regulation, of a unilateral Reform (Portugal), and of the 20th century marked by the disagreement between Portugal and Brazil, the more the political discourse emphasizes the role of the AO90 for the “unidade da língua” and for its international prestige, the more the enforcement of the AO90 in the Lusophone countries suffers from problems or uncertainties. The AO90 is thus a receptacle of graphic solutions that reflect orthoepic differences.